2014
DOI: 10.1007/s00277-014-2274-y
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of iron overload in patients with low-risk myelodysplastic syndrome: iron chelation therapy and organ complications

Abstract: This study aimed to evaluate the evolution of iron overload, assessed by serum ferritin (SF), in transfusion-dependent lower risk patients with myelodysplastic syndrome (MDS), as well as to describe the occurrence of organ complications, and to analyze its relationship with iron chelation therapy. This observational retrospective study was conducted from March 2010 to March 2011 in 47 Spanish hospitals. A total of 263 patients with lower risk MDS (International Prognostic Scoring System [IPSS] low/intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 35 publications
2
37
0
6
Order By: Relevance
“…[13] In myelodysplastic syndromes, different studies have suggested that iron-chelating agents may increase survival rates and reduce the risk of development into AML, although the molecular mechanism involved has not yet been elucidated and could involve a reduction in the production of free radicals, DNA damage and effect on mTOR and NFkB pathways. [14,15] In conclusion, we confirmed in this well-defined homogenous population of AML patients, the negative impact of high ferritin level before allo-HSCT on different outcomes. Moreover, our study has shown that iron-chelating agents in addition to their effect on normalizing ferritin levels after allo-HSCT and lowering toxic labile plasma iron, they have a significant impact on the incidence of relapse following allo-HSCT and could be implicated in apoptosis of erythroid precursors and DNA damage associated with malignant transformation.…”
supporting
confidence: 74%
“…[13] In myelodysplastic syndromes, different studies have suggested that iron-chelating agents may increase survival rates and reduce the risk of development into AML, although the molecular mechanism involved has not yet been elucidated and could involve a reduction in the production of free radicals, DNA damage and effect on mTOR and NFkB pathways. [14,15] In conclusion, we confirmed in this well-defined homogenous population of AML patients, the negative impact of high ferritin level before allo-HSCT on different outcomes. Moreover, our study has shown that iron-chelating agents in addition to their effect on normalizing ferritin levels after allo-HSCT and lowering toxic labile plasma iron, they have a significant impact on the incidence of relapse following allo-HSCT and could be implicated in apoptosis of erythroid precursors and DNA damage associated with malignant transformation.…”
supporting
confidence: 74%
“…However, the differences were not statistically significant. The IRON2 study from Spain, which found significantly longer overall survival and leukemia-free survival in chelated patients with lower risk MDS, also demonstrated significantly longer event-free survival regarding cardiac complications [40]. As already alluded to, iron overload may not only be related to cardiomyopathy but also to atherosclerosis.…”
Section: Nr Nrmentioning
confidence: 99%
“…List et al [27] Low/lnt-1 15% (n = 173) 15% (n = 52) 22% (n = 77) Gattermann et al [28] Low/lnt-1 21.5% (n = 247) 22% (r = 50) 13% (n = 100) Nolte et al [29] Low/lnt-1 11% (n = 50) NR NR Angelucci et al [30] Low/lnt-1 Transfusion independence in 15.5% (n = 152) Table 2 Clinical studies showing that iron chelation improves survival in patients with lower risk MDS [32][33][34][35][36][37][38][39][40].…”
Section: Is There a Survival Benefit From Chelation Therapy (Ict)?mentioning
confidence: 99%
“…Consequently, several retrospective and observational studies have suggested a beneficial influence of iron chelation on mortality and morbidity in MDS patients with transfusional IO [17][18][19][20][21][22][23][24].…”
Section: Potential Benefits Of Iron Chelation In Transfusion Dependenmentioning
confidence: 99%
“…Recently, several retrospective but also some prospective studies have indicated, that transfusion dependent patients with MDS might benefit from consequent iron chelation with regard to morbidity and mortality [17][18][19][20][21][22][23][24]. However, gastrointestinal adverse events leading to reduced quality of life in these patients are associated with low treatment adherence and are considered as a major obstacle in achieving consequent and effective iron chelation with DFX.…”
Section: Introductionmentioning
confidence: 99%